Russian pioneers : at the origins of non-objective art. - Nakov, Andrei Boris (London : Annely Juda Fine Art, 1976)
Altman, Nathan ; Annenkov, Yuri ; Archipenko, Alexandre ; Bortnyik, Sándor ; Burljuk, David ; Chashnik ; Exter, Alexandra ; Gontcharova, Natalia ; Kliun ; Klucis, Gustav ; Lissitzky, El ; Malevich, Kasimir ; Popova, Liubov ; Puni, Ivan ; Rodchenko, Alexander ; Stenberg, Georgii ; Suetin, Nikolai ; Tatlin, Vladimir
Frans & Engels
Russian pioneers at the origins of non-objective art, Annely Juda Fine Art, London, may 27 - september 18, 1976
boek
Keywords: Rusland